Indicadores de desempenho e competitividade de empresas associadas em rede: um estudo de multicasos de uma rede de agências de viagens e turismo do estado do Rio Grande do Sul - Braga, Daniele Penteado Gonçalves (2007)
This study shows the theme performance and competitiveness of 16 enterprises that are part of a net of travel and tourism agencies in the State of Rio Grande do Sul. Indicators have been developed to evaluate the period before the actual participation on the net and also the period after the participation on the net. The research is classified as qualitative. A deep interview with the net president and a questionnaire with the managers of the 16 companies were applied to collect data. The performance and competitiveness indicators were developed in a meeting with the managers of the companies that make part of this research. Between the 32 performance and competitiveness indicators analyzed in the companies that belong to the net, 25 indicators presented some improvement, 6 stayed as they were before and after the companies get into the net and only one presented a result lower than the one obtained before the companies start to make part of the net. In the 25 indicators that present some improvement there were: executive behavior, relations and partnerships with companies of the same industry, competitive advantage, motivation and satisfaction at work, improvement in the commissions generated by the providers, number of providers of negotiated products and monthly average incomes. About the performance indicators that stayed equal before and after the companies start to be a part of the net, it is possible to highlight the improve of the salaries. The only indicator that showed a decrease after the companies start to make part of the net was the one of the benefits generated by the providers. The results of this research indicates that the participation of the MPMES in a cooperation net improve their competitive performance.